Gospels and Grit : Work and Labour in Carlyle, Conrad, and Orwell - Breton, Rob, 1965- (Book collections on Project MUSE., 2005)
Examines the literary representations of work and labour in the Victorian works of Carlyle, and the 20th century writings of Conrad and Orwell.